Gabapentin as a drug with a broad potential. Presentation of its use in medical conditions beyond the official registration - Banasiak, Aleksandra Paulina; Pierzchała, Jakub Rafał; Bednarz, Katarzyna; Kasprowicz, Jakub; Banaś, Patryk; Sobańska, Natalia; Teichman, Rafał; Adamus, Justyna; Abram, Kamila; Hyjek, Michał (Journal of Education, Health and Sport, 2022)
Introduction: Gabapentin is a drug used for monotherapy or adjunctive therapy of simple and complex partial epileptic seizures in adults and children. It is also used to treat neuropathic pain for adults. There are reports in the medical literature of the effective use of gabapentin in the treatment of other conditions. Let’s take a closer look at its therapeutic potential. Aim of the study: The overview of current literature knowledge about the usage of gabapentin in various medical conditions within the fields of toxicology, dermatology, gynecology, psychiatry branches’ issues, with indicating the potential abuse. Materials and Methods: We reviewed the literature available in the PubMed database, using the keywords. Results: Gabapentin is an anticonvulsant drug structurally similar to gamma-aminobutyric acid (GABA). It is considered to be a centrally acting analog of GABA, nevertheless, it presents a different molecular mechanism comparing to the other drugs that affect GABA-ergic transmission. The registered indications for its use are the treatment of seizures within adults and children and neuropathic pain in adults. The literature reveals that gabapentin is also used in the treatment of alcohol abuse disorders within the patients with alcohol withdrawal symptoms, the treatment of pruritus, hot flashes during menopause and the treatment of anxiety disorder. Summary: Due to the ambiguous effects of gabapentin usage, it can be applied to treat various medical conditions. Nevertheless, the usage of this drug described in the literature requires additional studies on a larger group of patients to confirm the findings.